Lubuk Pusing Town, warriors and government ships: unsolved mystery in the history of Kedah, Malaysia - Mohd Kasri Saidon,; Rozalina Khalid, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Kedah is known as the oldest state in Malaysia and is also known as the nucleus state that represents the monarchy system with a very long historical line. Although the history of the monarchy is not widespread, the epic Merong Mahawangsa is said to be part of this historical background. The Kedah Al Tarikh Salasilah is in fact more histographic in nature; unfortunately, not all the historical events of the state was recorded. Focusing on Kedah’s history could help draw out the events which are still unsolved and can be said as questionable. The disappearance of the name Lubuk Pusing Town in Kuala Muda district, for instance, is one of the issues frequently mentioned. The commission of the government ship which also belonged to the Sultan has yet to be answered. The death of Kedah warriors which led to their invisibility in the history books has made this aspect of history an interesting area to be examined.